2011
DOI: 10.1038/ejcn.2011.97
|View full text |Cite
|
Sign up to set email alerts
|

Modifying effect of maternal nutritional status on the impact of maternal multiple micronutrient supplementation on birthweight in Indonesia

Abstract: Background/Objective: Low birthweight (LBW) and intrauterine growth restriction are linked with maternal nutritional status during pregnancy, and maternal supplementation with multiple micronutrients (MMNs) is reported to increase birthweight. Responses to MMN, however, might be modified by maternal nutrition. Subjects/Methods: To examine the differential effects of maternal nutritional status on birthweight responses to prenatal MMN supplementation, data from the Supplementation with Multiple Micronutrient In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 28 publications
(26 reference statements)
0
7
0
Order By: Relevance
“…the diet, body composition and lifestyle of the mother and to a lesser extent the father. There is considerable data from experimental studies in a range of animal species and prospective studies in humans that the mother’s diet and body composition before and in early pregnancy are related to phenotypic characteristics of the child, such as adiposity at birth and in childhood, and markers of cardiovascular risk such as carotid artery intima-media thickness [67-69]. The processes involved in influencing embryonic and fetal development are gradually being unravelled.…”
Section: Discussionmentioning
confidence: 99%
“…the diet, body composition and lifestyle of the mother and to a lesser extent the father. There is considerable data from experimental studies in a range of animal species and prospective studies in humans that the mother’s diet and body composition before and in early pregnancy are related to phenotypic characteristics of the child, such as adiposity at birth and in childhood, and markers of cardiovascular risk such as carotid artery intima-media thickness [67-69]. The processes involved in influencing embryonic and fetal development are gradually being unravelled.…”
Section: Discussionmentioning
confidence: 99%
“…Some human trials support the initial animal observations. For example, supplementation with iron and folic acid in pregnancy has been shown to increase birthweight but this response was modified by maternal nutritional status, with infants born to women with better shortterm nutrition having greater birthweight response [164] . Whether there is an epigenetic basis to these observations similar to those reported for the rat models is not well established although it has been suggested that alterations at the H19 differentially methylated region is a likely mechanism by which folic acid risks and/or benefits are conferred in utero [165] .…”
Section: Critical Windows Of Development and Avenues For Interventionmentioning
confidence: 99%
“…Pregnant women who received MMN supplementation had similar characteristics to those receiving IFA. The characteristics of the children at 9–12 years of age whose mothers received MMN or IFA supplementation were also similar to the overall SUMMIT enrollees, as were the general characteristics of women in this study [ 38 , 45 ].…”
Section: Resultsmentioning
confidence: 59%